Tina: Empowerment Based Design for Domestic Violence Survivors Mobile Application - et.al, Emma Nuraihan Mior Ibrahim (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presentsa preliminary work on empowerment-based design mobile application prototype for those living with or identified as domestic violence (DV) survivors in Malaysia.By using Design Thinking method, we developed a mobile application which acts as a social support platform for DV survivors especially to those who are reluctant or unwilling to seek help. The study was conducted with Women’s Aid Organization (WAO), an NGO responsible for the provision of aid to domestic violence survivors in Malaysia. The aim of this project is to enhance TINA (Think I Need Aid) services provided by WAO.For the prototype design, the study proposed five (5) categories of empowerment features which include (i) screening and assessment, (ii) emergency response (iii) evidence reporting (iv) preventative and (v) self-efficacy andempowerment. The prototype was then tested and evaluated in terms of its functionality and practicality with 10 participants representing various stakeholders. A qualitative analysis was used to analyse the participant feedback. The paper concluded with discussion of the results and future works.